2017
DOI: 10.1002/pat.4084
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric microspheres: a delivery system for osteogenic differentiation

Abstract: Advanced drug delivery systems employing controlled release technology are being developed to address many of the difficulties associated with traditional methods of drug administration. Controlled release technology involves the use of devices such as polymer‐based disks, rods, pellets, or microspheres (MSs) that encapsulate drugs, genes, cytokines, and growth factors and release them in specific location within the body in a controlled fashion, for relatively long periods of time. Among these, microencapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 121 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…To date, bioactive inorganics, polymers, and composites are used to manufacture scaffolds. [5][6][7][8][9][10] FDA-approved poly(lactic-coglycolic acid) (PLGA) has good biocompatibility and is often prepared as scaffolds or microspheres for bone tissue repair. [11][12][13][14] Compared with 3D bulk framework scaffolds, microspheres can be directly injected to fill defects of different shapes without causing secondary damage.…”
Section: Introductionmentioning
confidence: 99%
“…To date, bioactive inorganics, polymers, and composites are used to manufacture scaffolds. [5][6][7][8][9][10] FDA-approved poly(lactic-coglycolic acid) (PLGA) has good biocompatibility and is often prepared as scaffolds or microspheres for bone tissue repair. [11][12][13][14] Compared with 3D bulk framework scaffolds, microspheres can be directly injected to fill defects of different shapes without causing secondary damage.…”
Section: Introductionmentioning
confidence: 99%
“…Strategy that sequentially releases growth factor and differentiation factor is commonly used [8,[17][18][19][20][21]. As per our knowledge, several review literatures have been published related to PLGA microspheres for biomedical applications [22][23][24][25]. However, a smaller number of reviews have been reported on the PLGA core-shell microsphere [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nanoparticles have been broadly utilized as drug delivery systems for targeted delivery of anticancer drugs [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in the pharmaceutical industry. They can enhance the delivery of hydrophobic drugs, decrease metabolic degradation of these drugs, target their delivery to malignant cancer cells just by the alteration of the surface of the delivery system with the addition of a ligand, and show controlled, extended or sustained delivery of drugs [ 7 , 8 , 13 , 25 , 53 , 58 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Introductionmentioning
confidence: 99%